1993
DOI: 10.1159/000278214
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the Development of Wisdom

Abstract: Recent psychological research into the realms and processes of growing wiser can be linked to gender theory and research documenting variation in human development. Drawing on an integrative model of wisdom including components in three domains (personality, cognition, and conation) and across three levels (intrapersonal, interpersonal, and transpersonal), we highlight potential differences in the ways that women and men attain and express wisdom, and we initiate a search for interactive patterns across the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
15

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 45 publications
0
26
1
15
Order By: Relevance
“…Orwoll and Achenbaum (1993) suggested that women might be higher than men in the affective aspects of aging, and men higher than women in the cognitive. This was partially supported by Ardelt (2009), who found that women were higher than men on the affective dimension, but that gender differences on the cognitive dimension were found only among older men and women.…”
Section: Sources Of Between Person Differences In Wisdommentioning
confidence: 99%
“…Orwoll and Achenbaum (1993) suggested that women might be higher than men in the affective aspects of aging, and men higher than women in the cognitive. This was partially supported by Ardelt (2009), who found that women were higher than men on the affective dimension, but that gender differences on the cognitive dimension were found only among older men and women.…”
Section: Sources Of Between Person Differences In Wisdommentioning
confidence: 99%
“…The transcendence of one's subjectivity and projections through (self-)reflection is likely to reduce one's self-centeredness. This, in turn, will permit deeper insights into one's own and others' motives and behavior, which enable a wise person to interact with people in a more constructive, sympathetic, and compassionate way [Achenbaum & Orwoll, 1991;Clayton & Birren, 1980;Csikszentmihalyi & Rathunde, 1990;Holliday & Chandler, 1986;Kramer, 1990;Orwoll & Achenbaum, 1993;Pascual-Leone, 1990]. Defined in this way, wisdom is a Weberian ideal type [Weber, 1980] that might rarely exist in reality.…”
Section: An Alternative Model Of Wisdom: Wisdom As a Three-dimensionamentioning
confidence: 99%
“…I propose, however, that those cognitive, reflective, and affective personality characteristics are also sufficient for wisdom to emerge, which makes this wisdom model relatively parsimonious. Other positive qualities that wise people are assumed to possess such as good judgment skills [Clayton, 1982;Dittmann-Kohli & Baltes, 1990;Kekes, 1983Kekes, , 1995Orwoll & Achenbaum, 1993;Sternberg, 1990bSternberg, , 1998], psychological health [Birren & Fisher, 1990;Kekes, 1983Kekes, , 1995Taranto, 1989], humor [Webster, 2003], autonomy [Kekes, 1983[Kekes, , 1995Rathunde, 1995], and a mature and integrated personality [Csikszentmihalyi & Rathunde, 1990;Kramer, 1990;Labouvie-Vief, 1990;Pascual-Leone, 1990] are hypothesized to be the product of a person's cognitive, reflective, and affective characteristics.…”
Section: Human Developmentmentioning
confidence: 99%
“…To know that one does not know, on the other hand, is likely to diminish one's self-centeredness and make one more humble (Csikszentmihalyi & Rathunde, 1990). Re ective thinking, the transcendence of one's negativities and projections, and a reduced self-centeredness, in turn, tend to increase a person's empathy, sympathy, and compassion for others (Achenbaum & Orwoll, 1991;Holliday & Chandler, 1986;Kramer, 1990;Orwoll & Achenbaum, 1993). As a result, wise people are more concerned about collective and universal issues than about their individual well-being (Clayton, 1982;Sternberg, 1990b).…”
Section: Effects On the Knowermentioning
confidence: 99%
“…This is why growing old is a necessary but not a suf cient condition for the emergence of wisdom (Moody, 1986 Because wisdom-related knowledge is timeless and universal its signi cance does not become dated and obsolete with time (Clayton, 1982;Clayton & Birren, 1980). Although the intellectual knowledge of wise elders may lag behind that of younger generations (Moody, 1986), they are a good source of advice for younger people, particularly in the areas of intra-or interpersonal matters and in cases of uncertainty (Blanchard-Fields & Norris, 1995;Clayton, 1982;Kekes, 1983;Orwoll & Achenbaum, 1993;Sternberg, 1990b).…”
Section: Relationship To Agingmentioning
confidence: 99%